STYLING CHARACTERISTICS OF BUSINESS CORRESPONDENCE IN GERMAN & UKRAINIAN LANGUAGES - Bashuk, N. P. (Advanced Education, 2014)
The article compares the structure of business correspondence between German and Ukrainian languages. Business correspondence is instrumental in establishing official, business and partner contacts between government institutions and private companies alike. It is also a major factor in building relationships between individuals. Business correspondence in Germany is defined by German Industry Standards (DIN 5008, 676) and has more requisite elements than it does in Ukraine. The differences lie in the format and placement of the date, the main text of German letter being divided into three parts versus two parts in Ukrainian, the signature in German letter is placed above the name of the author while Ukrainian letter has it across from author’s name. Ukrainian business letter does not call for specify its subject before the salutation. Common to both German and Ukrainian business letters is the use of a certain minimum of set expressions and stock phrases predicated upon a limited number of standard aspects of business writing which tend to be highly repetitive (letter of notification, request, proposal, demand, refusal, agreement). Covered herein are main types of German business letters (corporate partnership request letter, inquiry letter, business proposal letter, marketing letter, repeat offer letter, order letter, refusal letter, complaint letter, reminder letter), their characteristic features and typical stock phrases and set expressions. A grammatical analysis shows that business correspondence is marked by prevalence of present tense, more frequent use of active voice over passive, rather frequent occurrence of infinitive constructs with "zu" and imperative mood, rather infrequent occurrence of subordinate clauses - mainly noun, adjective and conditional clauses. Recent times are marked by a substantial reduction in use of subjunctive mood Konjunktiv II.